Optimization of Teaching and Learning Activities Using the Lecture Method in Fiqh Subjects During the Covid-19 Pandemic - Ani Maftukha (Manajia: Journal of Education and Management, 2025)
This study aims to describe a case related to the optimization of teaching and learning activities in Fiqh subjects during the Covid-19 pandemic. because this study was motivated by the emergence of the Covid-19 pandemic which currently requires teaching and learning activities to be carried out with Distance Learning (PJJ) or online. This study uses a qualitative approach with a descriptive type. In addition, this study will describe a phenomenon of teaching and learning activities that occur during Covid-19. The results of the study show that the productivity of fiqh learning is also one of the things that must be given as much as possible. For a Muslim, fiqh is a procedure for worship in everyday life such as prayer, infaq and alms. In this study, the method used is descriptive qualitative observation. The results of the study obtained are that there are several ways for educators and students who are able to provide optimal fiqh learning activities. The method used by educators is to give assignments, discussions, and questions and answers as well as motivation to students to follow fiqh learning with enthusiasm. Meanwhile, the way students do it is to divide their time between studying and relaxing, and to do the assignments given by the educators to be done by reading notebooks.